In the Question of Geospatial Information Data Use in the Forestry Legislation Making in Indonesia - Suparto Wijoyo; Wilda Prihatiningtyas; Indria Wahyuni; Dita Elvia Kusuma Putri; Ardhana Christian Noventry (Faculty of Law, Hasanuddin University, 2023)
The high rate of deforestation and many forest disputes in Indonesia show that forest management in Indonesia is not based on the principles of good forest governance. It also shows that there is still a lack of attention to the aspect of sustainable forest development which focuses on a balanced sustainability condition between the three forest functions (production, ecology, and socio-economic functions). Geospatial Information is expected to be the solution to help provide an accurate data and information which mapping forest development in accordance with the conditions of each forest area, so that the three functions can operate coherently. Furthermore, with the presence of integrated geospatial data, it can be used as a tool in policy formulation, decision making, and/or dispute resolution in the forestry sector. This paper applies empirical juridical research consisting participatory methods through discussions and interviews with related parties. In practice, the legal materials are firstly collected by using inventory and documentation. Then, it’s completed by interviews and Focus Group Discussion data. Moreover, it also applies statutory, conceptual, and case approaches. This paper highlights the use of geospatial information data in the forestry legislation making in Indonesia. Hence, this paper will present new information about the model of forestry dispute resolution based on geospatial information.